2019
DOI: 10.1101/682468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Lid/KDM5 histone demethylase complex activates a critical effector of the oocyte-to-zygote transition

Abstract: Following fertilization of a mature oocyte, the formation of a diploid zygote involves a series of coordinated cellular events that ends with the first embryonic mitosis. In animals, this complex developmental transition is almost entirely controlled by maternal gene products.How such a crucial transcriptional program is established during oogenesis remains poorly understood. Here, we have performed an shRNA-based genetic screen in Drosophila to identify genes required to form a diploid zygote. We found that t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…dhd encodes a thioredoxin-like protein that was previously described to be essential for sperm chromatin decompaction after fertilization [17]. The authors observed that dhd expression was severely reduced in Kdm5-depleted oocytes [5], which is in accordance with their recorded incapability of forming the paternal pronucleus. Importantly, Kdm5 depletion was associated with a sharp decrease of H3K4me3 across the dhd gene body, suggesting that Kdm5 directly regulates dhd expression.…”
Section: Competing Interestssupporting
confidence: 56%
See 2 more Smart Citations
“…dhd encodes a thioredoxin-like protein that was previously described to be essential for sperm chromatin decompaction after fertilization [17]. The authors observed that dhd expression was severely reduced in Kdm5-depleted oocytes [5], which is in accordance with their recorded incapability of forming the paternal pronucleus. Importantly, Kdm5 depletion was associated with a sharp decrease of H3K4me3 across the dhd gene body, suggesting that Kdm5 directly regulates dhd expression.…”
Section: Competing Interestssupporting
confidence: 56%
“…Not surprisingly, the loss of Kdm5 and its demethylase activity are associated with a significant reduction of female fertility [15]. Now Torres-Campana and colleagues [5] further expand the gamut of Kdm5-related functions during oogenesis to include the transcriptional regulation of deadhead (dhd)-a major player in the oocyte-to-zygote transition. dhd encodes a thioredoxin-like protein that was previously described to be essential for sperm chromatin decompaction after fertilization [17].…”
Section: Competing Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reasoned that changes in protein levels could be diagnostic of proteins with pivotal roles during the events of oocyte maturation and egg activation in Drosophila. Indeed, many known key regulators, such as GNU, LID and DHD, exhibit protein level patterns that are consistent with their functions during the transition ( Torres-Campana et al 2020 ; Kronja et al 2014a ; Petrova et al 2018 ). Similar to these proteins, many other proteins show protein level patterns suggestive of developmental control ( Kronja et al 2014a ).…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, Dhd plays crucial roles in the oocyte-to-embryo transition, where it reduces and modulates the activity of ribosomal and RNA-binding proteins, as well as that of the histone demethylase NO66 protein (18). Recently, it has also been reported that the transcriptional regulation of Dhd is modulated by the lysine-specific demethylase 5 (KDM5), a potent chromatin remodeler during female gametogenesis (19).…”
Section: Introductionmentioning
confidence: 99%